A Study on Screening of Glaucoma among Patients Attending Tertiary Eye Care Hospital at One of the Cities of Western India - Zainab S Dohadwala; Reema M Raval; Kintu S Shah; Jineel B Bhatt; Kinjal G Patel (Indian Association of Preventive and Social Medicine, 2022)
Introduction : Glaucoma is the leading cause of irreversible visual loss in world and also in India. Because of the relatively asymptomatic initial phase of the disease, it is often detected by chance and is frequently associated with extensive and irreversible damage at the time of diagnosis. Objectives:To screen for Glaucoma among patients eligible as per inclusion criteria, to classify the glaucoma cases according to clinical presentation and to correlate the occurrence of glaucoma with different variables. Method: The present study was conducted at one of the tertiary care hospitals of Ahmedabad city during celebration of "World Glaucoma Week - 2021". Total 1421 patients were offered opportunistic screening after oral informed consent during 6-12 March 2021, who attended the institute. After applying exclusion criteria, 945 were found eligible who underwent a comprehensive ophthalmic examination like visual acuity, intraocular pressure measurement, gonioscopy, optical disc and visual filed examinations were carried out as per standard protocols. Sociodemographic details, any relevant ophthalmic history pertaining to glaucoma and systemic illnesses were also assessed. The data were entered and analyzed in MS excel. Results: The incidence of newly diagnosed cases of glaucoma among opportunistic screened cohort was 36.71% (n=347). Of total newly diagnosed, the presentation as per clinical classification was as follows: Primary open angle glaucoma (POAG) - 202 (58.21%), Primary angle closure glaucoma (PACG) - 77 (22.19%), Primary angle closure suspect (PACS) - 41 (11.82%), Ocular hypertension (OHT) - 6 (1.73%), Normal tension glaucoma (NTG) - 10 (2.88%), Secondary glaucoma - 9 (7.09%) and Congenital glaucoma - 2 (0.58%). In yield, 25 (19.68%) were ≤40 years and 36 (28.35%) had positive family history of glaucoma. Conclusion: Presence of stand-alone Diabetes and Hypertension or presence of both accompanying - all three conditions were found to be statistically significant determinant for occurrence of particular variety of Glaucoma. There was highly significant statistical association between cup-disc ratio level at the time of presentation and clinical variety of glaucoma.